Formação continuada e desenvolvimento profissional dos docentes de administração - Aguiar, Victor Rafael Laurenciano (2012)
This paper aimed to know how the in-service teacher education contributes to the professional development of Business Administration professors. In addition to this main objective, three other secondary objectives were defined: to identify the professional teaching knowledge of the professors and how they developed this knowledge, if they develop their knowledge by their own and / or institutional initiatives and, finally, if they have the necessity for an ongoing updating. It was carried out a theoretical study based on many authors, for instance, Imbernón and Marcelo who were the main reference in relation to the professional development theme, while Tardif was the main one who provided the principles in relation to professional teaching knowledge. A survey research instrument was applied with 235 Business Administration professors, from 10 different community universities which are part of ACAFE System (Association of Santa Catarina educational foundations). It was noticed by the collected data that the initial assumption of this work, expressed in the research question that in-service teacher education contributes to the professional development, was correct, because despite all the limitations pointed out in the in-service teacher education offered currently by all institutions, professors still consider that it helps a lot . But it was possible to realize that there is a limited understanding of professional development, as a synonym for in-service teacher education and in this sense, it was confirmed that in-service teacher education could contribute effectively to professional development if it included (1) reflection on the experiential knowledge, (2) updating the knowledge of the specific field of Administration, (3) discussion of the role of the University and its institutional policies, (4) the curriculum of the course as a whole, (5) knowledge of reality and the students of the institution